Hubungan Tingkat Stres Dengan Pola Tidur Pada Mahasiswa Semester 7 Prodi Keperawatan S1 Fakultas Ilmu Kesehatan - Rizky Anggaresta Wijiyanti; Kris Linggardini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To examine the correlation between stress levels and sleep patterns in seventh semester undergraduate students of the Faculty of Health Sciences. Method: This study conducted using quantitative non-experimental research with descriptive correlation design with cross sectional approach. The sampling technique used total sampling with a sample size of 204. Results: The stress level of the seventh semester students at the Faculty of Health Sciences was in the moderate category (84.3). However, the sleep pattern was considered poor (90.7). Chi square test results showed that the correlation between stress levels and sleep patterns was p (0.001). Conclusion: There is a correlation between stress level and sleep pattern of nursing students of the Faculty of Health Science.